PENGARUH LATIHAN SPLIT SQUAT JUMP TERHADAP PENINGKATAN KECEPATAN TENDANGAN LURUS PADA ATLET PERGURUAN PENCAK SILAT PERSAUDARAAN SETIA HATI TERATE - Syamsul Arifin; Wahyudin Nur (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2014)
Effect  of  Exercise  Split  Squat  Jump  Kick  Against  Increased  Speed Straight In Athletes Pencak Silat Persaudaraan Setia Hati Terate (PSHT) Banjarmasin. The purpose of this study was to determine whether there is the effect of exercise Split Squat Jump to the increased speed straight kick in martial arts college athletes Persaudaraan Setia Hati Terate (PSHT) Banjarmasin.The method used in this study was a quasi-experimental method (Quasi- Experimental Reaserch). Design or design of the study using the one-group pretest- posttest  design.  Measurements  were  taken  before  and  after  treatment  was  given. Treatment effect is  measured from the difference between the initial measurement / pretest (Y1) and the final measurement / posttest (Y2).The  population  in  this  study  is  the  Athlete  Pencak  Silat  Pencak  Silat Persaudaraan Setia Hati Terate (PSHT) Banjarmasin, amounting to 35 people, and that the  research  samples  are  athletes  who  never  played  and  often  follow  the  practice amounted to 10 people with technical considerations porposif sampling or sample.Based on the conclusion of the study showed that: There was an increase in the speed of a straight kick in martial arts college athletes Brotherhood Terate Setia Hati (PSHT) Banjarmasin. Keywords: Split squat jump, speed martial arts kick straight